Review of spatial layout planning methods for regional multi-station integration - Zhou, Huiying; Zhang, Liting; Yang, Yongwen; Li, Qifen; Qian, Fanyue (Frontiers in Energy Research, 2024)
In order to accelerate the high-quality development of China's infrastructure, it is not only necessary to ensure the continuation and efficiency improvement of the original infrastructure, but also to promote the layout, implementation, improvement and quality improvement of new infrastructure. As an important part of the energy Internet and new power system, "multi-station integration" plays a role in strengthening digital transformation, intelligent upgrading, integration and innovation support, achieving the nearby integration of resources and the coordination and complementarity of operation, reducing redundant design, so that users, enterprises and industries in the region can reduce costs, energy saving and emission reduction, improve quality and efficiency. By combing the spatial layout planning methods, models and influencing factors of traditional single function station and multi-station integration in the region, the influences of the function station itself and other surrounding infrastructure on the function station are analyzed. Combined with the application scenario, load demand and integration mode of multi-station integration, it is proposed to combine common factors and characteristic factors. The objective evaluation method is introduced to improve the practicability and suitability of the layout location. Finally, the three-layer theoretical framework is proposed to improve and supplement the existing layout principles and methods, so as to provide reference suggestions for the scientific location selection and optimization of regional multi-station integration.